1996
DOI: 10.1080/10601329608010899
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of Blocked Isocyanate-Hydroxyl-Terminated Polybutadiene Cure Reaction

Abstract: The catalytic activity of three tertiary amines and three organotin compounds in the cure reaction of blocked isocyanate with hydroxylterminated polybutadiene was investigated. It was found that the steric factor determines the catalytic activity of the compound. The tin compounds showed higher catalytic activities than the amine compounds. The deblocking catalytic activity of the amine and tin compounds was confirmed by the identification of isocyanate functionality using infrared spectroscopy. The synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…24 For example, Muramatsu et al 25 reported that the deblocking reactions are related to the electron densities of these compounds and, therefore, can be predicted using computer-based simulation. Endo and co-workers 26 reported the transesterification of poly(N-acylurethanes) using various diols and triols at ambient temperatures.…”
Section: Transcarbamoylation Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…24 For example, Muramatsu et al 25 reported that the deblocking reactions are related to the electron densities of these compounds and, therefore, can be predicted using computer-based simulation. Endo and co-workers 26 reported the transesterification of poly(N-acylurethanes) using various diols and triols at ambient temperatures.…”
Section: Transcarbamoylation Reactionsmentioning
confidence: 99%
“…37 Amine and tin catalysts reportedly bring about synergistic effects in the deblocking reactions of phenol-blocked isocyanates. 24 Perhaps, the transcarbamoylation reaction of 4 using DBTDL and residual DABCO catalysts may be accelerated by such synergistic effects. This could be confirmed by allowing the transcarbamoylation reaction of 11, which has a similar structure but no residual catalyst present.…”
Section: Transcarbamoylation Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a continuation of a previous report, here we report the effect of metal alkoxides, metal phenoxides, tertiary amines, and organotin compounds on the preparation of poly(urethane imidine) copolymer with N ‐methyl aniline‐blocked prepolymer and bisphthalide. Metal alkoxides and phenoxides catalyze the blocked isocyanate–anhydride reaction,22 whereas tertiary bases and organotin compounds are known for their deblocking catalytic activity 23, 24. Studying the sensitivity of the blocked isocyanate–phthalide reaction against these two groups of compounds is the subject of this report.…”
Section: Introductionmentioning
confidence: 99%